Combine effects of robotic assisted gait training with transcranial magnetic stimulation on gait metrics and balance in stroke patients: a pilot randomized control - Jehangir, Abdullah; Ahmad, Irfan; Feng, Yali; Juan, Wang Wei; Chen, Ting; Yin, Ying (Frontiers in Neurology, 2025)
Background and objectiveStroke often causes gait and balance impairments due to disrupted neural control. While robotic-assisted gait training (RAGT) improves motor function, combining it with low-frequency transcranial magnetic stimulation (LF-rTMS) may enhance neuroplasticity and recovery. This pilot RCT investigates the feasibility and synergistic effects of RAGT + LF-rTMS on gait and balance in stroke patients.Materials and methodsThis pilot RCT included 21 stroke patients randomized into three groups: RAGT + active LF-rTMS, RAGT + sham rTMS, and control (standard physiotherapy). RAGT used an exoskeleton with adjustable speed (0.8–1.8 km/h) and body-weight support (40–60%). LF-rTMS (1 Hz, 80% RMT) targeted the unaffected hemisphere’s M1. Outcomes included 3D gait analysis (spatiotemporal metrics), dynamic balance (COP sway), and clinical scales (FMA-LE, BBS, MMT).ResultsThe RAGT+TMS group demonstrated more improvements in balance (BBS: Δ22.58 vs. Δ15.40 in RAGT+sham TMS; p = 0.05) and motor function (FMA: Δ5.86 vs. Δ1.61; p = 0.04) compared to other groups. Gait analysis revealed significant left step length increases in RAGT+TMS (Δ6.86 cm, p = 0.04), while balance metrics showed reduced postural sway (oscillation length: Δ − 25.01 cm, p = 0.04). All groups improved temporally (p < 0.01), but RAGT+TMS yielded synergistic enhancements in functional recovery.ConclusionThis study demonstrates that combined RAGT and LF-rTMS significantly enhances post-stroke motor recovery, yielding clinically superior improvements in balance (BBS), gait symmetry, and postural control compared to RAGT alone or conventional therapy. The synergistic effects highlight TMS’s potential to augment neuroplasticity when paired with robotic training. While further large-scale trials are needed, these findings support integrating dual-modality approaches for comprehensive stroke rehabilitation.Clinical trial registrationhttps://www.chictr.org.cn/indexEN.html, ChiCTR2200066978.